Prevention Efforts Against Drug Crimes by the Binmas Unit at the Depok Police Department - Brian Daven Kyher Gultom (Advances in Police Science Research Journal, 2021)
This research is motivated by the large number of drug crimes in the city of Depok which resulted in the large number of victims and perpetrators of crimes, whether it was distributing, using, inviting to use, and abusing. With that, it is necessary to have an effort that can reduce the occurrence of drug crimes, namely Precaution efforts from the Binmas Unit against drug crimes. The author conducted a study to find out how the Precaution carried out by the Binmas unit against drug crimes, what efforts were made by the Binmas unit in preventing drug crimes, what were the factors that influenced the Binmas unit in preventing drug crimes. This research was conducted with a qualitative approach, using descriptive analysis research methods, as well as data collection techniques with interviews, observations, and document studies. The results of the study found that the implementation of Precaution by the Binmas unit against drug crimes at the Depok Metro Police was not optimal so that the number of victims and perpetrators continued to increase in committing drug crimes. Then, there are internal and external factors that become obstacles in preventing drug crimes from being hampered by the Binmas unit. Based on the results of the study, the researchers suggest to remind and provide socialization of a continuous approach to the residents of Depok City so that the occurrence of drug crimes does not increase, the management process must be improved again so that the implementation of work is real, and needs to be conveyed to the leadership for additional personnel, namely asking for help. additional personnel from outside agencies.